Vascular Fluorescence Imaging Control for Complex Renal Artery Aneurysm Repair Using Laparoscopic Nephrectomy and Autotransplantation - Matteo Tozzi; Luigi Boni; Gabriele Soldini; Marco Franchin; Gabriele Piffaretti (Case Reports in Transplantation)
Intraoperative fluorescent imaging using indocyanine green enables vascular surgeons to confirm the location and states of the reconstructed vessels during surgery. Complex renal artery aneurysm repair involving second order branch vessels has been performed with different techniques. We present a case of ex vivo repair and autotransplantation combining the advantages of minimally invasive surgery and indocyanine green enhanced fluorescence imaging to facilitate vascular anatomy recognition and visualization of organ reperfusion.